Lebanon Economic Monitor, Fall 2018 : De-Risking Lebanon - World Bank (World Bank, Washington, DC, 2018)
Lebanon's macro-financial conditions are currently under heavy scrutiny as the country faces increasing challenges. The risk profile for Lebanon is rising sharply in light of the convergence of a number of negative local and global factors, including global monetary conditions. Meanwhile, the utility of some of the tools used by the central bank is depleting following years of application. The central bank has responded by beefing up its stock of foreign exchange reserves, lengthening the maturity of deposits and limiting the liquidity available, thereby inhibiting speculation against the Lebanese Pound. In this issue of the Lebanon Economic Monitor (LEM), we focus on Lebanon's macrofinancial conditions. We begin by explaining real economy and macro-fiscal features that underpin these conditions. We then present a synopsis on the intertwining monetary and financial sectors, followed by an elucidation on latest macrofinancial dynamics. Naturally, the role and activity of the central bank is given particular attention.